A dinâmica do movimento pela educação e a luta pela terra no Médio Mearim. - Silva, Edson Sousa da (2015)
This paper presents an analysis of the interpretation of the Agricultural Family Schools in Maranhão and the dynamics of the process of struggle and conquest of the land and the struggle for a differentiated education model in the Médio Mearim , Maranhão State . Was held in Schools stones Poção de Pedras , Lago do Junco , São Luiz Gonzaga do Maranhão and Vitorino Freire, the Middle Mearim region and interviewed leaders, students, alumni, monitors and founders of EFA's. Another focus of this work is to voice the babassu coconut breakers and rural workers who lived conflict situations on the ground, the process of joint mobilization drives and reflections on the education of children / youth / students of the region. Discuss still which fields of struggle and the concept of Family Agricultural School , in the view of social workers surveyed , considering the support and incentive, difficulties in maintaining the operation and community ideals, school, family and farm. When trying to analyze the narratives 'll bring this work, we intuit that they serve for an initial self-reflection process of social movements and mobilization units on what is the desired differentiated education by babassu coconut breakers and rural workers in the region and the Médio Mearim realize the reflectivity in the case of Agricultural Family Schools . Finally reflections 'll bring this work place highlighted that the initial goals is maintained or created other, linking the struggle for land situation the question of the permanence of young people in the field and the relationship with agriculture.